Sentencing equilibrium in rape cases: a legal and political explanation of jurisdictional uniformity in China - Moulin Xiong; Yiwei Xia; Xiaohong Yu (Humanities & Social Sciences Communications)
Abstract Sentencing disparity dominates in American scholarship and has been leading global research in past decades, however, few studies have addressed sentencing equilibrium across countries. Learning from the previous theories regarding court communities, organizational conformity, and so on, this paper develops a theory of jurisdictional uniformity to address sentencing equilibrium in embedded courts across different levels in China. With data on sentence length consisting of 15,142 rape offenders nationwide, this article conducts bivariate and multilevel multivariate analyses to demonstrate negligible sentencing differences across cities and provinces. Authors believe the sentencing rules under jurisdictional uniformity pave the way for balanced sentencing, while the political mechanism in the judicial system controls jurisdictional disparity. Given that the existence of sentencing disparity should be seriously rechecked in each jurisdiction due to the legal and political diversity across the country, attention should be given to sentencing equilibrium inside the embedded court.